STRATEGI KEPALA SEKOLAH DALAM MANAJEMEN KONFLIK SEBAGAI UPAYA MEWUJUDKAN KINERJA TEAMWORK DI MI NU II PONTIANAK - Muftahatus Saadah; Gismina Tri Rahmayati; Elfina Saely; Shaleh Shaleh (STKIP Pesisir Selatan, 2022)
In running an organization, conflicts are always present and cannot be avoided by every member of the organization. Usually conflict is naturally present in any cooperative relationship between individuals and groups. Conflict will be positive if it can be managed properly through conflict management built by a leader in his or her own right. The principal becomes a leader in running the organization of the school's educational institution. The role of the principal of MI Nahdlatul Ulama II is certainly required to be able to manage the conflicts that occur in MI Nahdlatul Ulama II. This study aims to find out how the strategy or type of handling carried out by the principal in conflict management as an effort to realize teamwork performance. The method used in this research is qualitative research and the type of research, which includes field research using phenomenological design. The method used in this research is qualitative research and the type of research, which includes field research using phenomenological design. The results of this study show that principals manage conflicts with strategies of collaboration, accommodation, and compromise. Through these three ways of handling conflicts, the principal is proven to prevent, avoid, and be able to minimize the impact of conflict in the MI Nahdlatul Ulama II Pontianak school environment, as well as the realization of teamwork performance where the principal and all teachers can contribute according to their capacity and ability so that the team can achieve the best results.